"The Effect Of Cervıcal Headgear On The Frankfort Mandıbular Plane Angle" - Oktay Üner; Sevil Akkaya (Galenos Yayinevi, 1988)
In this study, the effect of cervical headgear treatment, for reearning the space losses due to early maxiller second deciduous molar extraction or extensive crown destruction, on the vertical position of mandible has been discussed. To this end, 60 profile head roentgenograms of 30 individual which have been taken before and after the treatment have been evaluated. 15 cases, treated with cervical traction have had this treatment with a mean of 8.5 months and the other 15 cases which consist of control group have been followed for 10 months without any treatment. On the roentgenograms, in addition to FMA angle GoGnSN, SN/ANS-PNS angles and, X and Y dimensions for assessing the extrusion and distalisation of upper first molars have been evaluated. An increase in the Y dimension; which shows extrusion with cervical headgear treatment has been observed in both groups, but this increase has been found significant only in the treatment group. While there is a mesialisation of first upper molars in the control group, there is a distalisation in the treatment group, and this difference between the groups is significant. The reduction of FMA angle measurements are not significant when compared between the groups.